Verotoxin Receptor-Based Pathology and Therapies - Lingwood, Clifford (Frontiers in Cellular and Infection Microbiology, 2020)
Verotoxin,VT (aka Shiga toxin,Stx) is produced by enterohemorrhagic E. coli (EHEC) and is the key pathogenic factor in EHEC-induced hemolytic uremic syndrome (eHUS-hemolytic anemia/thrombocytopenia/glomerular infarct) which can follow gastrointestinal EHEC infection, particularly in children. This AB5 subunit toxin family bind target cell globotriaosyl ceramide (Gb3), a glycosphingolipid (GSL)(aka CD77, pk blood group antigen) of the globoseries of neutral GSLs, initiating lipid raft-dependent plasma membrane Gb3 clustering, membrane curvature, invagination, scission, endosomal trafficking and retrograde traffic via the TGN to the Golgi, and ER. In the ER, A/B subunits separate and the A subunit hijacks the ER reverse translocon (dislocon-used to eliminate misfolded proteins-ER associated degradation-ERAD) for cytosolic access. This property has been used to devise toxoid based therapy to temporarily block ERAD and rescue the mutant phenotype of several genetic protein misfolding diseases.